Arginine Induced Streptococcus gordonii Biofilm Detachment Using a Novel Rotating-Disc Rheometry Method - Gloag, Erin S.; Wozniak, Daniel J.; Wolf, Kevin L.; Masters, James G.; Daep, Carlo Amorin; Stoodley, Paul (Frontiers in Cellular and Infection Microbiology, 2021)
Oral diseases are one of the most common pathologies affecting human health. These diseases are typically associated with dental plaque-biofilms, through either build-up of the biofilm or dysbiosis of the microbial community. Arginine can disrupt dental plaque-biofilms, and maintain plaque homeostasis, making it an ideal therapeutic to combat the development of oral disease. Despite our understanding of the actions of arginine towards dental plaque-biofilms, it is still unclear how or if arginine effects the mechanical integrity of the dental plaque-biofilm. Here we adapted a rotating-disc rheometry assay, a method used to quantify marine biofilm fouling, to study how arginine treatment of Streptococcus gordonii biofilms influences biofilm detachment from surfaces. We demonstrate that the assay is highly sensitive at quantifying the presence of biofilm and the detachment or rearrangement of the biofilm structure as a function of shear stress. We demonstrate that arginine treatment leads to earlier detachment of the biofilm, indicating that arginine treatment weakens the biofilm, making it more susceptible to removal by shear stresses. Finally, we demonstrate that the biofilm disrupting affect is specific to arginine, and not a general property of amino acids, as S. gordonii biofilms treated with either glycine or lysine had mechanical properties similar to untreated biofilms. Our results add to the understanding that arginine targets biofilms by multifaceted mechanisms, both metabolic and physical, further promoting the potential of arginine as an active compound in dentifrices to maintain oral health.